Evaluating dysphagia and xerostomia outcomes following transoral robotic surgery for patients with oropharyngeal cancer. Issue 12 (7th October 2021) - Mehta, Mitesh P.; Prince, Rebecca; Butt, Zeeshan; Maxwell, Bryce E.; Carnes, Brittni N.; Patel, Urjeet A.; Stepan, Katelyn O.; Mittal, Bharat B.; Samant, Sandeep
Abstract: Background: We assessed long‐term patient‐reported dysphagia and xerostomia outcomes following definitive surgical management with transoral robotic surgery (TORS) in patients with oropharyngeal cancer (OPC) via a cross‐sectional survey study. Methods: Patients with OPC managed with primary oropharyngeal surgery as definitive treatment at least 1 year ago between 2015 and 2019 were identified. The M. D. Anderson Dysphagia Inventory (MDADI) and Xerostomia Inventory (XI) scores were compared across treatment types (i.e., no adjuvant therapy [TORS‐A] vs. adjuvant radiotherapy [TORS+RT] vs. adjuvant chemoradiotherapy [TORS+CT/RT]). Results: The sample had 62 patients (10 TORS‐A, 30 TORS+RT, 22 TORS+CT/RT). TORS‐A had clinically and statistically significantly better MDADI scores than TORS+RT ( p = 0.03) and TORS+CT/RT ( p = 0.02), but TORS+RT and TORS+CT/RT were not significantly different. TORS‐A had clinically and statistically significantly less XI than TORS+RT ( p < 0.01) and TORS+CT/RT ( p < 0.01). Conclusions: Patients with OPC who have undergone TORS+RT or TORS+CT/RT following surgery face clinically worse dysphagia and xerostomia outcomes relative to patients who undergo TORS‐A.